Method for increasing the life of a carbon fiber insulation cylinder and carbon fiber insulation cylinder

CN118955149BActive Publication Date: 2026-11-03ZHEJIANG XINGHUI NEW MATERIALS TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411056675.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2026-11-03
Estimated Expiration
2044-08-02

AI Technical Summary

Technical Problem

[0004]然而,现有技术提供的碳纤维保温筒在真空高温炉中会受到反应气体的腐蚀,并且高温环境下的腐蚀进程较快,这使得碳纤维保温筒的实际使用寿命并不是很长

Benefits of technology

[0025]本发明通过对浸有粘结溶液的软毡基体进行共热处理,得到的碳纤维保温筒包裹层具有较高耐侵蚀性,可增加碳纤维保温筒的使用寿命。并且,该包裹层在不损伤保温筒胚体的情况下易更换,从而进一步延长了碳纤维保温筒的使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118955149B_ABST
    Figure CN118955149B_ABST
Patent Text Reader

Abstract

The application provides a method for prolonging the service life of a carbon fiber heat preservation cylinder and the carbon fiber heat preservation cylinder, and belongs to the technical field of heat preservation cylinder preparation. The method comprises the following steps: step 1, soaking a contact surface of a soft felt matrix in contact with the surface of the heat preservation cylinder in a bonding solution; step 2, baking the soft felt matrix after being soaked for 5-20 minutes; the duration of the first baking is 0.5-3 hours, and the temperature is 50-80 DEG C; step 3, after the first baking is completed, the contact surface is combined and pasted with the surface of the heat preservation cylinder, and then the second baking is performed after a fastening ring is added; the duration of the second baking is 1-3 hours, and the temperature is 100-200 DEG C. Through the co-heat treatment of the soft felt matrix soaked in the bonding solution, the obtained wrapping layer of the heat preservation cylinder has high corrosion resistance, and the wrapping layer is also easy to replace without damaging the heat preservation cylinder blank, so that the service life of the heat preservation cylinder is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermal insulation cylinder manufacturing technology, and in particular to a method for increasing the lifespan of carbon fiber thermal insulation cylinders and a carbon fiber thermal insulation cylinder. Background Technology

[0002] With the rapid development of solar energy and semiconductors, the demand for thermal insulation materials in their production equipment has become increasingly prominent, and the requirements for these materials are also becoming more stringent. They not only require energy conservation and emission reduction, but also high oxidation resistance, high temperature resistance, and corrosion resistance. These requirements are continuously driving the rapid development of the thermal insulation materials industry.

[0003] Carbon fiber insulation cylinders possess advantages not found in traditional insulation materials, including rigidity, self-support, high strength, no short fiber shedding, and low thermal conductivity. They are primarily used in vacuum furnaces and various metallurgical industrial furnaces. With the rapid development of the polycrystalline silicon and monocrystalline silicon industries, the demand for high-quality carbon fiber insulation cylinders, as ideal insulation materials for high-temperature furnace thermal fields, has reached new heights. Existing technologies, such as the method for preparing high-performance carbon fiber insulation cylinders disclosed in publication number CN115259880A, produce insulation cylinders with high density, compressive strength, and thermal insulation performance.

[0004] However, existing carbon fiber insulation cylinders are susceptible to corrosion by reaction gases in vacuum high-temperature furnaces, and the corrosion process is rapid under high-temperature conditions, resulting in a relatively short service life. Furthermore, once the insulation cylinder is corroded, the corroded carbon residue falls into the furnace, contaminating the products and rendering the entire batch unusable. Therefore, this technical field urgently needs to solve the corrosion resistance problem of insulation cylinders in vacuum high-temperature furnaces. Summary of the Invention

[0005] One of the technical problems to be solved by the present invention is the corrosion resistance of carbon fiber insulation cylinders in vacuum high-temperature furnaces in the prior art.

[0006] To solve the above-mentioned technical problems, the present invention employs a method of wrapping a layer of soft felt around the outer layer of a carbon fiber insulation cylinder, wherein the bonding surface between the soft felt and the carbon fiber insulation cylinder is obtained by heat treatment with a bonding solution. The specific details are as follows:

[0007] On one hand, embodiments of the present invention provide a method for increasing the lifespan of carbon fiber insulation cylinders. The method includes:

[0008] Step 1: Immerse the contact surface between the soft felt substrate and the surface of the insulation cylinder blank in the adhesive solution;

[0009] Step 2: Bake the soft felt substrate after soaking for 5-20 minutes; the baking time is 0.5-3 hours and the temperature is 50-80℃.

[0010] Step 3: After the first baking is completed, the contact surface is bonded to the surface of the insulation cylinder blank, and a fastening ring is added before a second baking is performed; the second baking time is 1-3 hours and the temperature is 100-200℃.

[0011] In practice, the soaking time can be any of 5 min, 8 min, 11 min, 14 min, 18 min, or 20 min; the first baking time can be any of 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, or 3 h, and the first baking temperature can be any of 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, or 80℃; the second baking time can be any of 1 h, 1.5 h, 2 h, 2.5 h, or 3 h, and the second baking temperature can be any of 100℃, 120℃, 140℃, 160℃, 180℃, or 200℃.

[0012] In some embodiments, the thickness of the soft felt substrate is 5-20 mm, and the immersion depth of the contact surface is 0.2 to 0.25 times the thickness of the soft felt substrate.

[0013] In practice, the thickness of the soft felt substrate can be any value among 5mm, 8mm, 12mm, 15mm, 17mm, and 20mm; the immersion depth of the contact surface is 0.2 to 0.25 times the thickness of the soft felt substrate, for example, any value among 1mm, 2mm, 4mm, and 5mm.

[0014] In some embodiments, the soft felt matrix is ​​one of three types: polyacrylonitrile-based soft felt, bitumen-based soft felt, and adhesive-based soft felt.

[0015] In some embodiments, the adhesive solution components include:

[0016] 10-25% phenolic curing epoxy resin, 15-25% silicon carbide powder, 10-15% graphite powder, 40-60% deionized water, 0.5-3% silane coupling agent γ-methacryloxypropyltrimethoxysilane, 1-5% polyethylene glycol, 0.5-3% sodium polyacrylate.

[0017] In some embodiments, the epoxy value of the phenolic curable epoxy resin is greater than 0.5 eq / 100g; the silicon carbide powder has a mesh size of 500-1500 and a purity of >98%; and the graphite powder has a mesh size of 500-2000 and a purity of >98%.

[0018] In some embodiments, the adhesive solution components include: 10-25% water-soluble phenolic resin, 10-25% polycarbosilane, 15-20% boron nitride powder, 50-70% deionized water, 1-3% γ-aminopropyltriethoxysilane, and 0.5-3% polyvinylpyrrolidone.

[0019] In some embodiments, the binder solution components include: the residual carbon content of the water-soluble phenolic resin is 32-38%; and the boron nitride powder has a mesh size of 1000-3000 and a purity >99%.

[0020] In some embodiments, the adhesive solution components include: 15-30% high residual carbon phenolic resin, 15-30% polysilazane, 10-30% zirconium oxide, 50-60% deionized water, 0.5-2% vinyltrimethoxysilane, and 1-3% polyoxyethylene ethyl ether.

[0021] In some embodiments, the binder solution components include: the high carbon residue phenolic resin having a carbon residue content of 47-52%; and the zirconium oxide having a mesh size of 1000-2500.

[0022] In some embodiments, the insulation cylinder blank obtained in step 3 is placed in a carbonization furnace at 800-1100°C for 3-8 hours to obtain the finished insulation cylinder.

[0023] In practice, the carbonization temperature can be any value among 800℃, 850℃, 900℃, 950℃, 1000℃, and 1100℃; the carbonization time can be any value among 3h, 4h, 5h, 6h, 7h, and 8h.

[0024] On the other hand, embodiments of the present invention provide a heat-insulating cylinder. The heat-insulating cylinder is manufactured using the method described in the first aspect above.

[0025] This invention utilizes a heat treatment process on a soft felt substrate impregnated with an adhesive solution to obtain a carbon fiber insulation cylinder wrapping layer with high corrosion resistance, thereby increasing the service life of the carbon fiber insulation cylinder. Furthermore, this wrapping layer is easily replaceable without damaging the insulation cylinder blank, further extending the service life of the carbon fiber insulation cylinder.

[0026] In addition, after the soft felt and the adhesive solution are subjected to co-heat treatment, the soft felt has a high-temperature resistant bonding effect on the outer surface of the carbon fiber insulation cylinder, which can achieve long-term bonding in a vacuum high-temperature environment and prevent the soft felt from falling off due to insufficient bonding strength at high temperatures. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1The microstructure of the adhesive solution on the soft felt surface after carbonization is shown in Example 1. Detailed Implementation

[0029] The embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples. The detailed description of the following embodiments and the accompanying drawings are used to illustrate the principles of the present invention by way of example, but should not be used to limit the scope of the present invention. The present invention can be implemented in many different forms and is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

[0030] These embodiments are provided to make the invention thorough and complete, and to fully express the scope of the invention to those skilled in the art. It should be noted that, unless otherwise specifically stated, the relative arrangement of components and steps, material composition, numerical expressions, and values ​​set forth in these embodiments should be interpreted as merely exemplary and not as limiting.

[0031] It should be noted that, in the description of this invention, unless otherwise stated, "a plurality of" means two or more; the terms "upper," "lower," "left," "right," "inner," and "outer," etc., indicating orientation or positional relationships, are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0032] Furthermore, the terms "first," "second," and similar terms used in this invention do not indicate any order, quantity, or importance, but are merely used to distinguish different parts. Terms such as "comprising" or "including" mean that the element preceding the term encompasses the element listed after the term, and do not exclude the possibility of encompassing other elements as well.

[0033] All terms used in this invention have the same meaning as understood by one of ordinary skill in the art to which this invention pertains, unless otherwise specifically defined. It should also be understood that terms defined in general dictionaries should be interpreted as having meanings consistent with their meanings in the context of the relevant art, and not as idealized or highly formalized, unless expressly defined herein.

[0034] Techniques, methods, and equipment known to those skilled in the art may not be discussed in detail, but where appropriate, they should be considered part of the specification.

[0035] The specific embodiments of the present invention are as follows:

[0036] On one hand, embodiments of the present invention provide a method for increasing the lifespan of carbon fiber insulation cylinders. The method includes:

[0037] Step 1: Immerse the contact surface between the soft felt substrate and the surface of the insulation cylinder blank in the adhesive solution;

[0038] Step 2: Bake the soft felt substrate after soaking for 5-20 minutes; the baking time is 0.5-3 hours and the temperature is 50-80℃.

[0039] Step 3: After the first baking is completed, the contact surface is bonded to the surface of the insulation cylinder blank, and a fastening ring is added before a second baking is performed; the second baking time is 1-3 hours and the temperature is 100-200℃.

[0040] In practice, the soaking time can be any of 5 min, 8 min, 11 min, 14 min, 18 min, or 20 min; the first baking time can be any of 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, or 3 h, and the first baking temperature can be any of 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, or 80℃; the second baking time can be any of 1 h, 1.5 h, 2 h, 2.5 h, or 3 h, and the second baking temperature can be any of 100℃, 120℃, 140℃, 160℃, 180℃, or 200℃.

[0041] In practice, the baking temperature for the first baking stage is set at 50-80℃. This temperature ensures that the moisture in the adhesive solution is dried while the resin remains in a gel-like but not fully cured state. This guarantees effective bonding between the soft felt substrate and the insulation cylinder blank after the substrate is applied to the surface of the insulation cylinder blank.

[0042] In practice, the temperature for the second baking is set at 100-200℃ to allow the resin in the adhesive solution to solidify, thus ensuring a stable bond between the soft felt matrix and the insulation cylinder blank.

[0043] The present invention uses a technique of attaching soft felt to the surface, which enables repeated replacement of the soft felt, thereby reducing the wear and tear and replacement frequency of the insulation cylinder.

[0044] This embodiment achieves a carbon fiber insulation cylinder wrapping layer with high corrosion resistance by co-heating a soft felt substrate impregnated with an adhesive solution, thereby increasing the service life of the carbon fiber insulation cylinder. Furthermore, this wrapping layer is easily replaceable without damaging the insulation cylinder blank, further extending the service life of the carbon fiber insulation cylinder. Simultaneously, the co-heating treatment of the soft felt and adhesive solution provides high-temperature adhesion to the outer surface of the carbon fiber insulation cylinder, enabling long-term bonding under vacuum and high-temperature environments and preventing the soft felt from detaching due to insufficient bonding strength at high temperatures.

[0045] In some embodiments, the thickness of the soft felt substrate is 5-20 mm, and the immersion depth of the contact surface is 0.2 to 0.25 times the thickness of the soft felt substrate.

[0046] In practice, the thickness of the soft felt substrate can be any value among 5mm, 8mm, 12mm, 15mm, 17mm, and 20mm; the immersion depth of the contact surface is 0.2 to 0.25 times the thickness of the soft felt substrate, for example, any value among 1mm, 2mm, 4mm, and 5mm.

[0047] In practice, soft felt with a thickness of less than 5mm provides poor protection, while a thickness greater than 20mm can cause the surface of the soft felt to collapse due to its relatively poor bonding strength. Therefore, this implementation uses soft felt with a thickness of 5-20mm as the soft felt substrate.

[0048] In the specific implementation process, in order to ensure that the soft felt does not completely adhere to the outer surface of the insulation barrel without collapsing, the soaking depth in this embodiment is determined to be 0.2 to 0.25 times the thickness of the soft felt substrate, specifically 1-5 mm. This range of values ​​ensures that the soft felt does not collapse while also ensuring incomplete adhesion, making subsequent replacements easier.

[0049] In some embodiments, the soft felt matrix is ​​one of three types: polyacrylonitrile-based soft felt, bitumen-based soft felt, and adhesive-based soft felt.

[0050] In some embodiments, the adhesive solution components include:

[0051] 10-25% phenolic curing epoxy resin, 15-25% silicon carbide powder, 10-15% graphite powder, 40-60% deionized water, 0.5-3% silane coupling agent γ-methacryloxypropyltrimethoxysilane, 1-5% polyethylene glycol, 0.5-3% sodium polyacrylate.

[0052] In some embodiments, the epoxy value of the phenolic curable epoxy resin is greater than 0.5 eq / 100g; the silicon carbide powder has a mesh size of 500-1500 and a purity of >98%; and the graphite powder has a mesh size of 500-2000 and a purity of >98%.

[0053] In some embodiments, the adhesive solution components include: 10-25% water-soluble phenolic resin, 10-25% polycarbosilane, 15-20% boron nitride powder, 50-70% deionized water, 1-3% γ-aminopropyltriethoxysilane, and 0.5-3% polyvinylpyrrolidone.

[0054] In some embodiments, the binder solution components include: the residual carbon content of the water-soluble phenolic resin is 32-38%; and the boron nitride powder has a mesh size of 1000-3000 and a purity >99%.

[0055] In some embodiments, the adhesive solution components include: 15-30% high residual carbon phenolic resin, 15-30% polysilazane, 10-30% zirconium oxide, 50-60% deionized water, 0.5-2% vinyltrimethoxysilane, and 1-3% polyoxyethylene ethyl ether.

[0056] In some embodiments, the binder solution components include: the high carbon residue phenolic resin having a carbon residue content of 47-52%; and the zirconium oxide having a mesh size of 1000-2500.

[0057] In some embodiments, the insulation cylinder blank obtained in step 3 is placed in a carbonization furnace at 800-1100°C for 3-8 hours to obtain the finished insulation cylinder.

[0058] In practice, the carbonization temperature can be any value among 800℃, 850℃, 900℃, 950℃, 1000℃, and 1100℃; the carbonization time can be any value among 3h, 4h, 5h, 6h, 7h, and 8h.

[0059] On the other hand, embodiments of the present invention provide a heat-insulating cylinder. The heat-insulating cylinder is manufactured using the method described in the first aspect above.

[0060] To enable those skilled in the art to better understand the usage methods provided in the embodiments of the present invention, the following detailed explanation is provided through specific experiments and structures:

[0061] The carbon fiber insulation cylinders in the following specific embodiments are manufactured using the content disclosed in paragraphs 0004-0027 of patent number CN115259880B. The resulting insulation cylinder blank is hereinafter referred to as the blank.

[0062] Example 1

[0063] 1. Grind and polish the surface of the blank until it is smooth.

[0064] 2. Prepare the bonding solution. The components of the bonding solution are:

[0065] ① 21% phenolic curing epoxy resin (main selection criteria: epoxy value > 0.5 eq / 100g, viscosity < 500 cp), 18% high-purity silicon carbide powder (mesh size 500-1500), 12% high-purity graphite powder (mesh size 500-2000), 40% deionized water, 2% silane coupling agent γ-methacryloxypropyltrimethoxysilane (KH-570), 4% polyethylene glycol (PEG), and 3% sodium polyacrylate (PAA-Na). Stir for 15 minutes to prepare a binder solution.

[0066] 3. Prepare the soft felt substrate, and select 15mm adhesive-based soft felt.

[0067] 4. Cut the selected soft felt substrate to the required length. Soak the contact surface between the soft felt and the insulation cylinder in the adhesive solution. The soaking depth of the contact surface should be 3mm, depending on the depth of the soft felt.

[0068] 5. After soaking for 15 minutes, place the soft felt in an oven at 70℃ and bake for 1.5 hours.

[0069] 6. After baking, attach the side of the soft felt that has been soaked in the solution to the surface of the insulation cylinder, secure it with a fastening ring, and then bake it again in an oven at 170℃ for 1.5 hours.

[0070] 7. Place the baked insulation cylinder into a carbonization furnace at 900℃ for 8 hours to obtain the finished product.

[0071] Figure 1 The diagram shows the microstructure of the adhesive solution on the surface of the soft felt after carbonization in Example 1. Figure 1 The microstructure diagram shows that the interface between the reinforced solution, prepared in a certain proportion, and the insulation cylinder substrate is dense and uniformly distributed.

[0072] Example 2

[0073] The operation process in this embodiment is similar to that in Example 1, the difference being the preparation of the adhesive solution. Specifically: ① 25% phenolic curable epoxy resin (main selection criteria are epoxy value greater than 0.5 eq / 100g, viscosity < 500cp), 25% high-purity silicon carbide powder (mesh size 500-1500), 15% high-purity graphite powder (mesh size 500-2000), 24% deionized water, 3% silane coupling agent γ-methacryloxypropyltrimethoxysilane (KH-570), 5% polyethylene glycol (PEG), and 3% sodium polyacrylate (PAA-Na). Stir for 20 minutes to prepare the adhesive solution.

[0074] Example 3

[0075] The operation process in this embodiment is similar to that in Example 1, the difference being the preparation of the adhesive solution. Specifically: ① 10% phenolic curing epoxy resin (main selection criteria are epoxy value greater than 0.5 eq / 100g, viscosity < 500cp), 15% high-purity silicon carbide powder (mesh size 500-1500), 10% high-purity graphite powder (mesh size 500-2000), 59% deionized water, 1.5% silane coupling agent γ-methacryloxypropyltrimethoxysilane (KH-570), 2.5% polyethylene glycol (PEG), and 2% sodium polyacrylate (PAA-Na). Stir for 10 minutes to prepare the adhesive solution.

[0076] Example 4

[0077] 1. Grind and polish the surface of the blank until it is smooth.

[0078] 2. Prepare the bonding solution. The components of the bonding solution are:

[0079] A binder solution is prepared by stirring for 20 minutes with 20% water-soluble phenolic resin (mainly selected based on 35% residual carbon), 25% polycarbosilane, 15% high-purity boron nitride powder (mesh size 1000-3000, purity >99%), 37% deionized water, 2% γ-aminopropyltriethoxysilane (KH-550), and 1% polyvinylpyrrolidone.

[0080] 3. Prepare the soft felt substrate, and select 15mm adhesive-based soft felt.

[0081] 4. Cut the selected soft felt substrate to the required length. Soak the contact surface between the soft felt and the insulation cylinder in the adhesive solution. The soaking depth of the contact surface should be 3mm, depending on the depth of the soft felt.

[0082] 5. After soaking for 15 minutes, place the soft felt in an oven at 70℃ and bake for 1.5 hours.

[0083] 6. After baking, attach the side of the soft felt that has been soaked in the solution to the surface of the insulation cylinder, secure it with a fastening ring, and then bake it again in an oven at 170℃ for 1.5 hours.

[0084] 7. Place the baked insulation cylinder into a carbonization furnace at 900℃ for 8 hours to obtain the finished product.

[0085] Example 5

[0086] The operation process in this embodiment is similar to that in Example 4, except that the composition of the adhesive solution is as follows: 25% water-soluble phenolic resin, 25% polycarbosilane, 20% boron nitride powder, 24% deionized water, 3% γ-aminopropyltriethoxysilane, and 3% polyvinylpyrrolidone.

[0087] Example 6

[0088] The operation process in this embodiment is similar to that in Example 4, except that the composition of the adhesive solution is as follows: 10% water-soluble phenolic resin, 10% polycarbosilane, 15% boron nitride powder, 63.5% deionized water, 1% γ-aminopropyltriethoxysilane, and 0.5% polyvinylpyrrolidone.

[0089] Example 7

[0090] 1. Grind and polish the surface of the blank until it is smooth.

[0091] 2. Prepare the bonding solution. The components of the bonding solution are:

[0092] 20% high-carbon phenolic resin (carbon residue between 47-52%), 20% polysilazane, 15% zirconium oxide (mesh size 1000-2500), 41% deionized water, 2% vinyltrimethoxysilane (VTMO), and 2% polyoxyethylene ethyl ether (POE). Stir for 20 minutes to prepare a binder solution.

[0093] 3. Prepare the soft felt substrate, and select 15mm adhesive-based soft felt.

[0094] 4. Cut the selected soft felt substrate to the required length. Soak the contact surface between the soft felt and the insulation cylinder in the adhesive solution. The soaking depth of the contact surface should be 3mm, depending on the depth of the soft felt.

[0095] 5. After soaking for 15 minutes, place the soft felt in an oven at 70℃ and bake for 1.5 hours.

[0096] 6. After baking, attach the side of the soft felt that has been soaked in the solution to the surface of the insulation cylinder, secure it with a fastening ring, and then bake it again in an oven at 170℃ for 1.5 hours.

[0097] 7. Place the baked insulation cylinder into a carbonization furnace at 900℃ for 8 hours to obtain the finished product.

[0098] Example 8

[0099] The operation process of this embodiment is similar to that of Example 7, the only difference being the composition ratio of the adhesive solution: 30% high residual carbon phenolic resin, 30% polysilazane, 30% zirconium oxide, 5% deionized water, 2% vinyltrimethoxysilane, and 3% polyoxyethylene ethyl ether.

[0100] Example 9

[0101] The operation process in this embodiment is similar to that in Example 7, except that the composition of the adhesive solution is as follows: 15% high residual carbon phenolic resin, 15% polysilazane, 10% zirconium oxide, 58.5% deionized water, 0.5% vinyltrimethoxysilane, and 1% polyoxyethylene ethyl ether.

[0102] Example 10

[0103] The operation process of this embodiment is similar to that of Embodiment 1, except that the adhesive-based soft felt in Embodiment 1 is replaced with PAN-based soft felt.

[0104] Example 11

[0105] The operation process of this embodiment is similar to that of Embodiment 1, except that the adhesive-based soft felt in Embodiment 1 is replaced with asphalt-based soft felt.

[0106] The finished insulation cylinders prepared according to the above embodiments were placed in a nitrogen atmosphere to measure their respective service time. The equipment used was a high-temperature furnace, and the nitrogen atmosphere temperature in the furnace was 2000℃. Specific experimental data are as follows:

[0107] Table 1. Service life test results of the insulation cylinders prepared in Examples 1-9

[0108] Example 1 2 3 4 5 6 7 8 9 10 11 Time (h) 755 652 517 623 582 518 598 639 555 608 569

[0109] As can be seen from the data of Example 1 in Table 1, the insulation cylinder made using the optimal solution of the present invention can achieve a service life of more than 700 hours in actual use. After 700 hours, if the insulation cylinder is basically undamaged, it can be reused by simply replacing the reinforcing felt on the surface. This effectively reduces the cost of use and increases the stability during use, reducing the risk of product quality degradation or product scrapping in high-temperature furnaces due to insulation cylinder damage.

[0110] Comparative Example 1

[0111] The purpose of this invention is to enhance the corrosion resistance of the insulation cylinder and increase its service life. Specifically, a soft felt layer is adhered to the surface of the existing insulation cylinder to form a wrapping layer. Therefore, this comparative example still uses a carbon fiber insulation cylinder made according to the disclosure in paragraphs 0004-0027 of patent number CN115259880B as the control group. A total of 5 control groups were prepared, and their service life was tested using the same testing method as in the above embodiments. The specific experimental data are as follows: 421, 390, 357, 418, and 425.

[0112] As shown in Table 1, the experimental data reveals that, compared to the existing insulation cylinders with a lifespan of 350-430 hours, the insulation cylinders obtained using the method provided by this invention have a lifespan exceeding 500 hours, with some reaching over 700 hours. This demonstrates that the method provided by this invention significantly extends the lifespan of the insulation cylinder.

[0113] Those skilled in the art will know that when high-density carbon fiber insulation cylinders are used in vacuum high-temperature furnaces, most failures are caused by leakage of corrosive reactive gases through the gap between the heater and the insulation cylinder, leading to damage or failure. The method provided by this invention solves the problem of high-density insulation cylinders being susceptible to corrosion in vacuum high-temperature furnaces, and avoids the situation where corrosion of the insulation cylinder causes carbon slag to fall from its surface, contaminating the products inside the furnace and resulting in the scrapping of the entire batch of products. This increases the stability and lifespan of the insulation cylinder. Furthermore, the protective felt on the surface can be repeatedly replaced without damage to the insulation cylinder substrate, extending the service life of the insulation cylinder by more than double.

[0114] Examples 12-14

[0115] The operation process of Examples 12-14 is similar to that of Example 1, the only difference being the soaking time. The specific soaking times were 5 min, 10 min, and 20 min, respectively. The measured service lives were 716, 722, and 704, respectively. This data shows that the soaking time has little impact on the service life; high service life values ​​can be obtained within the range of 5-20 min.

[0116] Examples 15-16

[0117] The operation process of Examples 15-16 is similar to that of Example 1, the only difference being the baking time and temperature. Specifically, the time and temperature were: baking at 50℃ for 0.5 hours and baking at 80℃ for 3 hours. The measured service lives were 724 and 743, respectively. From this data and the test results of Example 1, it can be determined that the baking temperature for one baking session can be 50-80℃, and the time can be 0.5-3 hours. Under these conditions, it is possible to ensure that the moisture in the adhesive solution is dried while the resin in the adhesive solution remains in a gel-like but not cured state. This ensures that the soft felt substrate can effectively bond to the surface of the insulation cylinder blank after being attached.

[0118] Examples 17-18

[0119] The operation process of Examples 17-18 is similar to that of Example 1, except for the time and temperature of the second baking. Specifically, the time and temperature are as follows: baking again in an oven at 100℃ for 1 hour, and then baking again in an oven at 200℃ for 3 hours. The measured service lives are 749 and 761, respectively. Based on this data and the test results of Example 1, the temperature for the second baking is determined to be 100-200℃, and the time can be determined to be 1-3 hours. Under these conditions, the resin in the adhesive solution can be fully cured, ensuring a stable bond between the soft felt matrix and the insulation cylinder blank.

[0120] Examples 19-20

[0121] The operation process of Examples 19-20 is similar to that of Example 1, the only difference being the thickness of the soft felt substrate and the immersion depth of the contact surface. Specifically, the thickness of the soft felt substrate is 5mm, and the immersion depth of the contact surface is 0.2 times the thickness of the soft felt substrate, i.e., 1mm; the thickness of the soft felt substrate is 20mm, and the immersion depth of the contact surface is 0.25 times the thickness of the soft felt substrate, i.e., 5mm. The measured service life is 744 and 758 respectively. From this set of data and the test results of Example 1, it can be seen that: 1. A soft felt with a thickness of 5-20mm as a soft felt substrate can achieve a good protective effect, and the bonding force of the soft felt of this thickness can prevent the surface soft felt from collapsing; 2. The immersion depth is determined to be 0.2 to 0.25 times the thickness of the soft felt substrate, which can ensure that the soft felt does not collapse and also ensure incomplete adhesion, making subsequent replacement easier.

[0122] The various embodiments of the present invention have now been described in detail. To avoid obscuring the concept of the invention, some details known in the art have not been described. Those skilled in the art will fully understand how to implement the technical solutions disclosed herein based on the above description.

[0123] While specific embodiments of the present invention have been described in detail by way of examples, those skilled in the art should understand that the above examples are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art should understand that modifications can be made to the above embodiments or equivalent substitutions can be made to some technical features without departing from the scope and spirit of the invention. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any manner.

Claims

1. A method for increasing the lifespan of carbon fiber insulation cylinders, characterized in that, The method includes: Step 1: Immerse the contact surface between the soft felt substrate and the surface of the insulation cylinder blank in the adhesive solution; Step 2: Bake the soft felt substrate after soaking for 5-20 minutes; the baking time is 0.5-3 hours and the temperature is 50-80℃. Step 3: After the first baking is completed, the contact surface is bonded to the surface of the insulation cylinder blank, and a fastening ring is added before a second baking is performed; the second baking time is 1-3 hours and the temperature is 100-200℃. The thickness of the soft felt substrate is 5-20 mm, and the immersion depth of the contact surface is 0.2-0.25 times the thickness of the soft felt substrate; Step 4: Place the insulation cylinder blank obtained in Step 3 into a carbonization furnace at 800-1100℃ for 3-8 hours to carbonize, and obtain the finished insulation cylinder. The adhesive solution components are any one of the following groups: Group 1: 10-25% phenolic curing epoxy resin, 15-25% silicon carbide powder, 10-15% graphite powder, 40-60% deionized water, 0.5-3% silane coupling agent γ-methacryloxypropyltrimethoxysilane, 1-5% polyethylene glycol, 0.5-3% sodium polyacrylate. The second group: The adhesive solution components include: 10-25% water-soluble phenolic resin, 10-25% polycarbosilane, 15-20% boron nitride powder, 50-70% deionized water, 1-3% γ-aminopropyltriethoxysilane, and 0.5-3% polyvinylpyrrolidone. The total percentage of all components in the second group is 100%. The third group: The adhesive solution components include: 15-30% high residual carbon phenolic resin, 15-30% polysilazane, 10-30% zirconium oxide, 50-60% deionized water, 0.5-2% vinyltrimethoxysilane, 1-3% polyoxyethylene ethyl ether, and the total percentage of all components in the third group is 100%.

2. The method according to claim 1, characterized in that, The soft felt matrix is ​​one of three types: polyacrylonitrile-based soft felt, bitumen-based soft felt, and adhesive-based soft felt.

3. The method according to claim 1, characterized in that, When the adhesive solution component is the first group, the epoxy value of the phenolic curable epoxy resin is greater than 0.5 eq / 100g; the mesh size of the silicon carbide powder is 500-1500 and the purity is >98%; the mesh size of the graphite powder is 500-2000 and the purity is >98%.

4. The method according to claim 1, characterized in that, When the adhesive solution component is the second group, the adhesive solution component includes: the residual carbon content of the water-soluble phenolic resin is 32-38%; the mesh size of the boron nitride powder is 1000-3000, and the purity is >99%.

5. The method according to claim 1, characterized in that, When the adhesive solution component is the third group, the adhesive solution component includes: the residual carbon content of the high residual carbon phenolic resin is 47-52%; and the mesh size of the zirconium oxide is 1000-2500.

6. A heat-insulating cylinder, characterized in that, The heat-insulating cylinder is manufactured using the method described in any one of claims 1-5.

Citation Information

Patent Citations

  • Preparation method of high-performance carbon fiber thermal insulation cylinder

    CN115259880A

  • A method for preparing a high-performance carbon fiber thermal insulation cylinder

    CN115259880B

  • Binding agent used for carbon materials in high-temperature furnace and application method

    CN103755375A